Characterization of surface-exposed structural loops as insertion sites for foreign antigen delivery in calicivirus-derived VLP platform - Panasiuk, Mirosława; Chraniuk, Milena; Zimmer, Karolina; Hovhannisyan, Lilit; Krapchev, Vasil; Peszyńska-Sularz, Grażyna; Narajczyk, Magdalena; Węsławski, Jan; Konopacka, Agnieszka; Gromadzka, Beata (Frontiers in Microbiology, 2023)
Chimeric virus-like particles (cVLPs) show great potential in improving public health as they are safe and effective vaccine candidates. Caliciviruses capsid protein has been described previously as a self-assembling, highly immunogenic delivery platform. The ability to significantly induce the cellular and humoral immunity can be used to boost the immune response to low immunogenic foreign antigens displayed on the surface of VLPs. Capsid proteins of Caliciviruses despite sequence differences share similar architecture with structural loops that can be genetically modified to present foreign epitopes on the surface of cVLPs. Here, based on the VP1 protein of Norovirus (NoV) we investigated the impact of the localization of the epitope in different structural loops of P domain of on the immunogenicity of the presented epitope. In this study three distinct loops of NoV VP1 protein were genetically modified to present multivalent influenza virus epitope consisting of tandem repeat of M2/NP epitopes. cVLPs presenting influenza virus conserved epitopes in different localizations were produced in the insect cells and used to immunize BALB/c mice. Specific reaction to influenza epitopes was compared in sera from vaccinated mice to determine if the localization of the foreign epitope has an impact on the immunogenicity.